SPEAKING DIFFICULTIES ANALYSIS IN PRONUNCING WORDS IN ENGLISH AT 5 YEAR OLD CHILDREN - Sirait, Tiofanny Elisabet; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This study aims to analyze the speech difficulties experienced by five-year-old children in pronouncing difficult words in English. Focusing on a child named M.B. from Pematangsiantar, this study explores various factors that influence his English pronunciation ability. Qualitative research methods were used to explore data from observations and interviews, which showed that environmental factors, phonological ability, and self-confidence play an important role in the language acquisition process. The results showed that M.B. had difficulty in pronouncing English sounds that did not exist in his mother tongue, as well as a lack of exposure to English in everyday life. This study provides insight into the challenges faced by children in learning a second language and the importance of environmental support in the language acquisition process.